2007
DOI: 10.1007/s00426-007-0115-5
|View full text |Cite
|
Sign up to set email alerts
|

The procedural learning of action order is independent of temporal learning

Abstract: How does learning the timing of actions influence our ability to learn the order of actions? A sequence of responses cued by spatial stimuli was learned in a serial reaction time task where the response-to-stimulus intervals (RSIs) were random, constant, or followed a fixed sequence. In this final sequenced-RSI condition, the response and RSI sequences were consistently matched in phase and could be integrated into a common sequence representation. The main result was that the response sequence was learned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The author showed that participants learned simultaneously about each of these two sequences to the same extent as did two control groups that were exposed to a single sequence. Analogous effects have been found by arranging a sequence of locations together with a temporal sequence in the response-to-stimulus intervals (Shin, 2008;Shin & Ivry, 2002).…”
Section: Sequence Learningmentioning
confidence: 87%
“…The author showed that participants learned simultaneously about each of these two sequences to the same extent as did two control groups that were exposed to a single sequence. Analogous effects have been found by arranging a sequence of locations together with a temporal sequence in the response-to-stimulus intervals (Shin, 2008;Shin & Ivry, 2002).…”
Section: Sequence Learningmentioning
confidence: 87%
“…Results showed implicit learning of the temporal structure without a correlated ordinal pattern in a single‐ but not multiple‐response SRT task. They argued that probabilistic uncertainty of an upcoming ordinal stimulus identity may explain the discrepancy (above) of why some previous studies (Miyawaki, 2006; O’Reilly et al., 2008; Shin, 2008; Shin & Ivry, 2002) had found no independent learning of temporal and ordinal patterns. Schultz et al.…”
Section: Which Musical Features Can Be Acquired?mentioning
confidence: 95%
“…This “problem of serial order” (Lashley, 1951) can be approached from different perspectives. On the one hand, work on sequence learning (e.g., Schuck, Gaschler, & Frensch, 2012; Shin, 2008) and representations of serial order (e.g., Botvinick & Bylsma, 2005; Botvinick & Plaut, 2006) has dealt with representations and processes securing precision of serial output with respect to order and timing based on sequence knowledge. On the other hand, work on the response selection bottleneck (Pashler, 1994) has dealt with the constraints that avoid parallel selection of responses despite parallel activation – for instance, when multiple stimuli are presented and multiple responses are required within the same trial.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, eyetracking work has revealed anticipatory processing (fixations to potential stimulus positions prior to stimulus onset) even with random sequences of stimulus positions (Marcus, Karatekin, & Markiewicz, 2006). On the other hand, anticipation of the time point of stimulus presentation (Shin, 2008) and response preparation (Bausenhart, Rolke, Hackley, & Ulrich, 2006) have been documented. This suggests that Task 2 processing might start prior to Stimulus 2 presentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation